Disaster Management and Information Technology Professional Response and Recovery Management in the Age of Disasters - Scholl, Hans Jochen; Holdeman, Eric E.; Boersma, F. Kees. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This edited book entertains a multitude of perspectives on crisis information management systems (CIMS)-based disaster response and recovery management. The use of information technology in disaster management has become the central means for collecting, vetting, and distributing information. It also serves as the backbone for coordination and collaboration between response and recovery units as well as resource management tool. This edited volume aims at covering the whole range of application and uses of CIMS in disaster response and recovery. It showcases coordination and collaboration mechanisms between government agencies, the involvement of non-governmental entities, lessons learned as well as lessons not learned, approaches to disaster resiliency in society, community engagement in disaster/catastrophe responses and recovery, and, particularly, the role of CIMS in response and recovery. Serving as a platform for showcasing recent academic discoveries as well as a knowledge source for practitioners, this volume will be of interest to researchers and practitioners interested in disaster response, public administration, emergency management, and information systems. .
1. Emergency Management's Journey with Technology -- 2. Deploying Modern Technology for Disaster Management Practitioners -- 3. Technology and information management supporting resilience in health care and rescue systems -- 4. A System for Collaboration and Information Sharing in Disaster Management -- 5. A decade of netcentric crisis management: challenges and future development -- 6. Common Operational Picture and Interconnected Tools for Disaster Response: the FASTER toolkit -- 7. Intelligent Building Evacuation: From Modeling Systems to Behaviors -- 8. Challenges of Integrating Advanced Information Technologies with 5G in Disaster Risk Management -- 9. An Integrated Framework to Evaluate Information Systems Performance in High-Risk Settings: Experiences from the iTRACK Project -- 10. Rural First Responders and Communication Technology: A Mixed Methods Approach to Assessing Their Challenges and Needs -- 11. Designing well-accepted IT solutions for emergency response: Methods and approaches -- 12. Mobile Device-to-Device Communication for Crisis Scenarios Using Low-cost LoRa Modems -- 13. Digitalized Cross-sector Collaboration for an Effective Emergency Response: Emerging Forms of Network Governance -- 14. Defining common information requirements for supporting inter-agency emergency operations -- 15. A Commercial Cloud-based Crisis Information Management System: How Fit and Robust is it in Response to a Catastrophe?- 16. Practitioners' Perceptions of Fitness to Task of a Leading Disaster Response Management Tool -- 17. From Digital Public Warning Systems to Emergency Warning Ecosystems -- 18. The role of Ontologies and Linked Open Data in support of Disaster Management -- 19. Towards a taxonomy for classifying Crisis Information Management Systems.
Keywords: Public administration; Technology -- Sociological aspects; Information technology; Application software; Public Administration; Public Management; Information and Communication Technologies (ICT).; Computer and Information Systems Applications